COVID-19-Related Brief Insomnia in a 13-Year-Old Adolescent Girl - Nihal Serdengeçti; Mahmut Cem Tarakçıoğlu (Sleep Science, 2024)
Neuropsychiatric manifestations that have developed after coronavirus disease 2019 (COVID-19) infection have not been fully clarified yet. Persistent insomnia and consequent significant impairment in daily functioning is an unexpected symptom of COVID-19 infection. In this case report, a 13-year-old female patient who presented with complaint of insomnia starting with COVID-19 infection is discussed. The patient showed significant improvement with melatonin treatment and maintained her wellbeing in the follow-up. Melatonin may be a useful option to treat COVID-19-related brief insomnia in adolescents. Our case report will be a step forward to help clinicians examine the underlying neurovegetative mechanisms, such as sleep, to improve patients wellbeing. HEADINGS: COVID-19. Melatonin. Sleep Initiation and Maintenance Disorders